Microvascularization of the thyroid glands in larval and adult Xenopus laevis‐ histomorphology and scanning electron microscopy of vascular corrosion casts. (11th March 2016) - Hopfinger, Mathias; Huber, Bettina; Lametschwandtner, Alois
Abstract: This study demonstrates gross arterial supply, venous drainage and microvascular patterns of larval and adult thyroid glands in the African Clawed Frog, Xenopus laevis by scanning electron microscopy of vascular corrosion casts and light microscopy of stained serial tissue sections. Results confirm published findings gained by microscopical dissections with respect to gross arterial supply. However, in adult frogs one rather than two thyroid veins are found. This study reveals for the first time that bilaterally located thyroid glands in premetamorphosis have immature capillary networks, lack a clear hierarchy of blood vessels, and show many signs of sprouting angiogenesis. During metamorphic climax, blood vessels gain a clear hierarchy and capillaries form closed networks around thyroid follicles. From climax onwards, non‐sprouting angiogenesis (intussusceptive microvascular growth) becomes the prevailing mode of angiogenesis intensifying follicle capillarization. Due to narrow interfollicular spaces, thyroidal arterioles remain superficial while draining venules are located interfollicularly. In contrast with the mammalian thyroid gland where most thyroid follicles have their own capillary beds, most thyroid follicles in Xenopus share their capillary beds with neighbouring follicles. Consequently, the concept of individual morphological and functional angiofollicular units applicable to adult mammalian and human thyroid glands is not applicable to larval and adult amphibian thyroid glands.